2005
DOI: 10.1557/jmr.2005.0184
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Molybdenum-doped Indium Oxide Thin Films Using Reactive Direct-current Magnetron Sputtering

Abstract: High-mobility molybdenum-doped In2O3 films (IMO) were prepared on the normal glass substrate by reactive direct current magnetron sputtering from the molybdenum-embedded indium metal target. The effects of oxygen partial pressure, substrate temperature, and sputtering current on the optoelectrical properties of IMO films were investigated. The films with the highest carrier mobility of 50 cm2 V−1 s−1, as well as the average visible transmission greater than 80% including the 1.2-mm-thick glass substrate, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
5
17
1
Order By: Relevance
“…The diffraction peaks corresponding to (2 1 1), (2 2 2), (4 0 0), and (4 4 0) planes are commonly present in most of the films. In samples with a statistical distribution of crystallites, the (2 2 2) reflection is the most intensive peak (I/I 0 = 100%), which is in good agreement with the earlier reports [8,9]. The relative intensity of (2 2 2) peak becomes smaller when the films are deposited with oxygen and annealed at temperatures P400°C in N 2 :H 2 atmosphere.…”
Section: Structural Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…The diffraction peaks corresponding to (2 1 1), (2 2 2), (4 0 0), and (4 4 0) planes are commonly present in most of the films. In samples with a statistical distribution of crystallites, the (2 2 2) reflection is the most intensive peak (I/I 0 = 100%), which is in good agreement with the earlier reports [8,9]. The relative intensity of (2 2 2) peak becomes smaller when the films are deposited with oxygen and annealed at temperatures P400°C in N 2 :H 2 atmosphere.…”
Section: Structural Studiessupporting
confidence: 91%
“…Li et al have reported the sputtered IMO films with amorphous structure [10] and crystalline structure [8] for the deposition at RT and 350°C, respectively. Generally, crystalline IMO films were reported only for the deposition at elevated temperatures, excepting to the high density plasma evaporated films by Sun et al [9].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, films with high mobility are obtained when substrates are heated during deposition. For instance, = 83 cm 2 V −1 s −1 was reported for films deposited by RF magnetron sputtering at T S = 350 • C from IMO target [10], = 80 cm 2 V −1 s −1 at T S = 290 • C by reactive environment hollow cathode sputtering from In and Mo metal targets [11], = 50 cm 2 V −1 s −1 at T S = 350 • C by reactive DC magnetron sputtering from a Mo-embedded In metal target [12], = 65.3 cm 2 V −1 s −1 at T S = 550 • C by reactive RF magnetron co-sputtering from In 2 O 3 and MoO 3 targets [13] and = 99 cm 2 V −1 s −1 at T S = 450 • C (with post-deposition heat treatment) by reactive RF magnetron cosputtering from ceramic In 2 O 3 and metallic Mo targets [14]. Alternatively, films deposited by sputtering without intentional substrate heating have been reported to have lower mobility values ( < 20 cm 2 V −1 s −1 ) [15][16][17].…”
Section: Introductionmentioning
confidence: 92%
“…proportion of Mo to In being 4%) with high optical transmittance and high carrier mobility by thermal reactive evaporation at substrate temperature 623 K. They have observed that molybdenum doped indium oxide (IMO) thin film shows high optical transmittance and high carrier mobility. Since then many researchers have explored this material by various deposition techniques including RF magnetron sputtering [4,[6][7][8], reactive dc magnetron sputtering [9], pulsed laser deposition PLD [10,11] and high density plasma evaporation [12]. In contrast to the conventional TCOs, IMO possess low bulk electric resistivity (ranging 1.7-2.4 Â 10 À6 O m), high carrier mobility (ranging 80-130 cm 2 /V s) with less NIR absorption [5] when deposited at elevated substrate temperature (623 K).…”
Section: Introductionmentioning
confidence: 99%